Acceptance, Effectiveness and Relationship of Blended Learning Implementation Among Lecturers in Polytechnic Sultan Mizan Zainal Abidin - Hasni bin Mahmood; Saupi bin Mohamed Noor (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Blended learning is one of the key pedagogical approaches being used in Higher Education Institutions in Malaysia. The latest e-learning technology has obvious potential in making polytechnics more competitive at the same time capable in producing good quality graduates and ready to compete in educational services globally. The main objective of this study is to identify the level of acceptance and impact of Blended Learning among lecturers in Polytechnic Sultan Mizan Zainal Abidin. Relative and non-dependent variable factors were used to test whether the lecturers' acceptance factor determines the level of implementation of this blended learning. A survey was conducted by using a set of questionnaire to collect quantitative data involving 270 respondents representing several academic departments in the Polytechnic of Sultan Mizan Zainal Abidin (PSMZA). The data were analyzed by using Statistical Package for Social Science (SPSS) version 20.0 software to obtain percentage values, frequency and mean scores. A pilot study found that the Alpha Cronbach's alpha was 0.933 and it showed a high level of reliability for the items tested. The scope of this study focuses on the level of acceptance and impact of Blended Learning only. Overall, respondents positively accept Blended Learning as part of learning and teaching process.